Perancangan Sistem Pemesanan Barang dan Jasa Berbasis IoT (Studi Kasus Pratama Laundry) - Ariyanto, Aditya Ichsan; Suryadi, Budi; Supratno, Setyo (JREC (Journal of Electrical and Electronics), 2020)
Laundry is a service that is growing very fast. The demands for laundry services in urban areas are very high since its start to become daily necessity. Currently, laundry services are still limited to manual services, where consumers will come directly or contact a laundry employee to pick up. It requires a process and time which is considered quite complicated. Other problems that arise are related to bookkeeping and the possibility of missing data from consumer orders because there is no real time order data. Researchers conducted research with the aim of designing an IoT-based laundry service ordering tool that utilizes Wemos D1 mini, so that order data can be sent in real time to Telegram. The research was conducted by taking a case study "Pratama Laundry" by taking data from consumers who ordered via touch sensor or google voice to be sent to Telegram.